2022
DOI: 10.1088/1748-605x/ac88ad
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, morphological, mechanical and biological performance of 3D printed poly(ϵ-caprolactone)/bioglass composite scaffolds for bone tissue engineering applications

Abstract: Several techniques, such as additive manufacturing, have been used for the manufacture of polymer-ceramic composite scaffolds for bone tissue engineering. A new extruder head recently developed for improving the manufacturing process is an experimental 3D printer Fab@CTI that enables the use of ceramic powders in the processing of composite materials or polymer blends. Still, the manufacturing process needs improvement to promotes the dispersion of ceramic particles in the polymer matrix. This article addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In vitro study on MC3T3 osteoblast cells revealed that the resultant hydrogel supports differentiation of cells thus concluded to be a promising scaffold for bone tissue engineering [ 134 ]. Recently Barbosa et al [ 135 ] developed scaffolds by 3D printing using mixtures of poly(ε-caprolactone) (PCL) and 45S5 Bioglass ®® , labeled as synthesised bioglass (SBG). The scaffolds achieved a compression modulus range from 54.4 ± 14.2 to 155.9 ± 20.4 MPa, which is within the range of compression modulus required for bone tissue engineering.…”
Section: Application Of Blends and Composites Of Bc In Tissue Enginee...mentioning
confidence: 99%
“…In vitro study on MC3T3 osteoblast cells revealed that the resultant hydrogel supports differentiation of cells thus concluded to be a promising scaffold for bone tissue engineering [ 134 ]. Recently Barbosa et al [ 135 ] developed scaffolds by 3D printing using mixtures of poly(ε-caprolactone) (PCL) and 45S5 Bioglass ®® , labeled as synthesised bioglass (SBG). The scaffolds achieved a compression modulus range from 54.4 ± 14.2 to 155.9 ± 20.4 MPa, which is within the range of compression modulus required for bone tissue engineering.…”
Section: Application Of Blends and Composites Of Bc In Tissue Enginee...mentioning
confidence: 99%